2022
DOI: 10.1139/cjce-2020-0671
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mix ratio of potato peel and pig manure on reaction kinetics and methane recovery from anaerobic co-digestion

Abstract: The potential improvement in methane recovery and reaction kinetics from different mixes of potato peel (PP) and pig manure (PM) in a single stage anaerobic co-digestion/mono-digestion process was investigated in a laboratory study. The highest methane yield of 231 mL/g TCODadded was observed in the 50:50 mix of potato peel and pig manure. Compared to the mono-digested substrates, co-digestion of PP and PM at 75:25, 50:50, and 25:75 synergistically improved methane yield by 17%, 25%, and 11%, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In another study, the semi-continuous co-digestion of potato and cabbage waste with 1:1 ratio led to the highest methane yield of 360 mL/g VS that was 18% and 24% higher than those obtained by the mono-digestion of potato waste and cabbage waste, respectively (Mu et al, 2017). Similarly, Adeleye et al (Adeleye et al, 2022) reported that the co-digestion of PPW and pig manure mixture with 50:50 ratio increases the methane yield by 25% over the mono-digested feedstocks (Table 4).…”
Section: Biogasmentioning
confidence: 81%
“…In another study, the semi-continuous co-digestion of potato and cabbage waste with 1:1 ratio led to the highest methane yield of 360 mL/g VS that was 18% and 24% higher than those obtained by the mono-digestion of potato waste and cabbage waste, respectively (Mu et al, 2017). Similarly, Adeleye et al (Adeleye et al, 2022) reported that the co-digestion of PPW and pig manure mixture with 50:50 ratio increases the methane yield by 25% over the mono-digested feedstocks (Table 4).…”
Section: Biogasmentioning
confidence: 81%
“…In addition to the production of biomethane, anaerobic digestion has become a potential component in wastewater treatment processes. It was employed to remove organic solids from various wastewater and sludge generated from different process industries and municipal solid or liquid wastes [87,90].…”
Section: Biomethanementioning
confidence: 99%
“…Achinas et al [39] stated that the maximum biogas production (485.4 mL/gVS) was obtained from acid pre-treatment of potato wastes/cow manure through anaerobic co-digestion. In addition, the methane output from combined potato wastes and pig manure (50:50 ratio) was improved by 25% compared to feedstocks that were mono-digested [16].…”
Section: Biogas Production From Potato Peel Wastesmentioning
confidence: 99%
“…The sustainable development of a circular green economy would be supported by the valorization of potato peel wastes throughout a biorefinery concept, which would be advantageous for the production of several bioproducts and the reduction in the final waste residue. Anaerobic digestion or fermentation of potato peel wastes to generate biofuels is referred to as biological processing [5,16]. In addition to the biological processing of potato peel wastes, thermochemical processing using pyrolysis, hydrothermal liquefaction, and hydrothermal carbonization is carried out to decompose potato peel wastes into the desired bioproducts [17].…”
Section: Introductionmentioning
confidence: 99%